Synthesis, Spectral Study and Theoretical Treatment of Some Mixing Ligand Complexes of Quinaldic Acid and 1, 10-Phenathroline (Baghdad Science Journal, 2016)
Metal complexes of Cu (II), Fe (III) and Mn (II) with Quinaldic acid (L1) and 1, 10-Phenathroline (L2) are synthesized and characterized by standaral physic- chemical procedures (element analysis, metal analysis, FTIR, Uv-Vis, magnetic moment and conductometeric measurements). On the base of these studies, mononuclear and six coordinated octahedral geometry and nonelectrolyte of these complexes have been proposed. The standard heat of formation (?Hºf) and binding energy (?Eb) for the free ligands and their complexes are calculated by using the PM3 method at 273K of Hyperchem.-8 program. The complexes are more stable than their ligands. Moreover, the electrostatic potential of free ligands are measured to investigate the reactive site of the molecules, PM3 is used to evaluate the vibrational spectra of the free ligands, the frequencies are obtained approximately agreed with those values experimentally found; in addition, the calculation helps to assign clearly the most diagnostic bands .